Situational Analysis and Expert Evaluation of the Nutrition and Health Status of Infants and Young Children in Five Countries in Sub-Saharan Africa. Issue 3 (September 2013) - Alles, Martine; Eussen, Simone; Ake-Tano, Odile; Diouf, Saliou; Tanya, Agatha; Lakati, Alice; Oduwole, Abiola; Mauras, Celine
Background: The poor feeding practices of pregnant women, infants, and young children contribute to the burden of malnutrition and subsequently to childhood morbidity and mortality in sub-Saharan Africa. Gaining insight into the nutritional and health status of infants and young children will help to focus future nutrition programs and actions. Objective: To assess the nutrition and health status of infants and young children in five sub-Saharan African countries: Ivory Coast, Senegal, Cameroon, Kenya, and Nigeria. Methods: Published and gray literature was critically reviewed and enriched with the views of local experts from academia, hospitals, and institutions to assess infants' and children's diet and health in the five sub-Saharan African countries. Subsequently, the Africa Nutriday Conference was held in Senegal in November 2011 to further discuss key challenges, action plans, and recommendations for future research. Results: This review highlighted the need for education of parents and healthcare professionals in order to increase their knowledge of breastfeeding, vaccination programs, and over- and undernutrition. An integrated health and nutrition surveillance is needed both to identify micronutrient deficiencies and to recognize early signs of overweight. These data will help to adapt nutrition education and food fortification programs to the target populations. Conclusions: Different countries in sub-Saharan Africa face similar nutrition and health issues and are currently not sharing best practices, nutrition programs, and scientific studies optimally. There is a need for closer collaboration among scientists within and between countries.